THE INFLUENCE OF ELECTRONIC WORD OF MOUTH ON PURCHASE INTENTION MEDIATED BY BRAND IMAGE ON INDOMIE INSTANT NOODLES IN BANDUNG CITY - Suryaman, Reykhan Ikhsan Suryaman; Elis Dwiana Ratnamurni (Economic and Bussiness Faculty, Dr Soetomo University, 2024)
This research aims to recognize the effect of electronic word- of- mouth on purchase intention which is mediated by the brand image of Indomie instant noodles in Bandung City. It is determined if the research instrument has passed the validity and reliability tests. This method is used to collect information from respondents, or active social media users of Generation Z who have not had time to buy Indomie instant noodle products as the subject of research evaluated as many as ninety respondents. Cross-sectional or one- shot research is the information collection procedure used. Multiple linear regression information analysis was conducted using the Sobel test and SPSS type 22 equipment. The four research hypotheses that have been put forward have empirical support. The results show that brand image can act as a mediating aspect in the bond between electronic word-of-mouth and purchase intention. Meanwhile, more scholars may advocate the use of alternative inspirations that directly influence purchase intention. Managers of comparable e-commerce businesses can also benefit from the findings of this research in terms of enhancing relevant strategies to improve the quality of this characteristic.